At the heart of Leadership How to get results with Emotional Intelligence - Freedman, Joshua (Freedom, Califonia Six Seconds Emotional Intelligence Press, 2019)
At the heart if leadership delivers a compelling case for leaders to attend to their own and their people's emotions as a critical asset for optimal performance. Then it shows you how. You'll learn the six seconds EQ Model, a practical three-step process to become more effective with emotions- plus use the code in the back of the book for a free assessment of your EQ talents.
Keywords: Leadership